RELEVANCE BETWEEN ISLAMIC FINANCE AND THE HALAL INDUSTRY ECOSYSTEM WITHIN THE FRAMEWORK OF GREEN BUSINESS - Hadi Peristiwo (Al-Muhasib: Journal of Islamic Accounting and Finance, 2024)
Indonesia is the country with the biggest Muslim population in the world, this actually could become a potential strategy for developing an economy based on halal industry. The halal industry is not only related to production but also becomes the source of funding or finance for its existence. For the halal industry to develop rapidly in the future, especially those related to green business, Islamic finance and financial services have a role to play in achieving a halal industrial ecosystem. The method used in this research is a literature review approach, namely research with a series of activities related to library data collection methods, reading and recording and processing research materials. The results showed that the halal industry is not only profit-oriented but also needs to pay attention to how the impacts arising from business activities are carried out. These impacts can improve the surrounding community where the Halal industry operates, the affected environment, the products it produces and how it treats its workers. Indonesia merupakan negara dengan populasi muslim terbesar di dunia, hal ini sebenarnya bisa menjadi strategi potensial untuk mengembangkan ekonomi berbasis industri halal. Industri halal tidak hanya berkaitan dengan produksi tetapi juga menjadi sumber pendanaan atau pembiayaan untuk keberadaannya. Agar industri halal dapat berkembang pesat di masa depan, terutama yang terkait dengan bisnis hijau, keuangan syariah dan jasa keuangan memiliki peran dalam mencapai ekosistem industri halal. Metode yang digunakan dalam penelitian ini adalah pendekatan tinjauan pustaka, yaitu penelitian dengan rangkaian kegiatan yang berkaitan dengan metode pengumpulan data perpustakaan, membaca dan mencatat serta mengolah bahan penelitian. Hasil penelitian menunjukkan bahwa industri halal tidak hanya berorientasi pada keuntungan tetapi juga perlu memperhatikan bagaimana dampak yang timbul dari kegiatan usaha dilakukan. Dampak ini dapat meningkatkan masyarakat sekitar tempat industri Halal beroperasi, lingkungan yang terkena dampak, produk yang dihasilkannya dan bagaimana mereka memperlakukan pekerjanya.